2012
DOI: 10.1109/tnnls.2012.2184801
|View full text |Cite
|
Sign up to set email alerts
|

Neural Learning Circuits Utilizing Nano-Crystalline Silicon Transistors and Memristors

Abstract: Properties of neural circuits are demonstrated via SPICE simulations and their applications are discussed. The neuron and synapse subcircuits include ambipolar nano-crystalline silicon transistor and memristor device models based on measured data. Neuron circuit characteristics and the Hebbian synaptic learning rule are shown to be similar to biology. Changes in the average firing rate learning rule depending on various circuit parameters are also presented. The subcircuits are then connected into larger neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Although ideal memristors are difficult to realize in practice, there are many different material systems and device structures that are close approximations. One of the main advantages of this network design is that circuit parameters are tunable to deal with asymmetric weight changes in non-linear devices [38]. Specifically, tuning can be accomplished by changing the injection voltage Vinj on the drain of the np-TFT (see Table 1) as well as the value of the feedback voltage pulse Vdep.…”
Section: B Memristive Devicesmentioning
confidence: 99%
“…Although ideal memristors are difficult to realize in practice, there are many different material systems and device structures that are close approximations. One of the main advantages of this network design is that circuit parameters are tunable to deal with asymmetric weight changes in non-linear devices [38]. Specifically, tuning can be accomplished by changing the injection voltage Vinj on the drain of the np-TFT (see Table 1) as well as the value of the feedback voltage pulse Vdep.…”
Section: B Memristive Devicesmentioning
confidence: 99%
“…1 College of Mathematics and Statistics, Hubei Normal University, Huangshi, 435002, China. 2 Institute for Information and System Science, Xi'an Jiaotong University, Xi'an, 710049, China. 3 School of Automation, Huazhong University of Science and Technology, Wuhan, 430074, China.…”
Section: Competing Interestsmentioning
confidence: 99%
“…In 2008, Hewlett-Packard research team [5] obtained a practical memristor device and exhibited its characteristic, such as nanoscale and the memory ability. It has been shown that memristors can be used to work as biological synapses in artificial neural network and replace resistor to simulate the human brain in memristor-based neural networks (MNNs) model, which would benefit many practical applications (see [6,7]). …”
Section: Introductionmentioning
confidence: 99%